If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3 + -9 + 8 = n + 2n + n Combine like terms: 3 + -9 = -6 -6 + 8 = n + 2n + n Combine like terms: -6 + 8 = 2 2 = n + 2n + n Combine like terms: n + 2n = 3n 2 = 3n + n Combine like terms: 3n + n = 4n 2 = 4n Solving 2 = 4n Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '-4n' to each side of the equation. 2 + -4n = 4n + -4n Combine like terms: 4n + -4n = 0 2 + -4n = 0 Add '-2' to each side of the equation. 2 + -2 + -4n = 0 + -2 Combine like terms: 2 + -2 = 0 0 + -4n = 0 + -2 -4n = 0 + -2 Combine like terms: 0 + -2 = -2 -4n = -2 Divide each side by '-4'. n = 0.5 Simplifying n = 0.5
| X^4-4x^3+8x-4=0 | | 3x/(x+1)+2/(x+2) | | 7x-29+21x=-9+2x | | ((-3x-10y)/2x)+((8x-8y)/2x) | | 14x-8=x+12 | | 9-6y=-10y-3 | | 96/4 | | 3x-7x+5=-6-1(4x-5) | | 8v=-16/3 | | 4y^2-5=19y | | (x-3)(x+3)=-5x-13 | | -3(y+12)=51 | | 28+b=15p | | 5s=7s+11-2s | | 54x-6(5x-12)= | | 5x-2+3x=3(x-2) | | 15-5(2x+14y)= | | (p+6)4-10= | | 6(b-2)-2b-1= | | -3(2x+1)=4(3x-5) | | 1-t-3tsquared=0 | | 8[7-(-2x-4)]=48x+152 | | 3+(12-1)(-4/3) | | 8-x=3x | | x^4-8x^3+7x^2-3x-36=0 | | 2/5(y+4/5)=4/5(y-1/5) | | r(r+11)-88= | | r^2+11r-88= | | 25x+6=3x-(8x+6) | | x/6=36x | | 16x-15x-9x=13 | | -9x=12-(2x-3) |